Light- and temperature-sensitive seizures are regulated by spatially distinct cortex glial populations in the central nervous system - Govind Kunduri; Tanja Angela Godenschwege; Katherine Sankey; Kandahalli Venkataranganayaka Abhilasha; Usha Acharya; Jairaj K. Acharya (Proceedings of the National Academy of Sciences, 2026)
Epilepsy is characterized by recurrent seizures due to abnormal neuronal activity originating from a population of neurons. Seizures are often associated with abnormal glial cell function at the seizure focus. Studies have shown that each glial type, such as astrocytes, displays a significant degree of heterogeneity in their development, molecular signatures, and function depending on the brain region in which they are located. It is unknown, however, if such heterogeneity differentially influences or causes seizures. Previous studies in Drosophila have shown that aberrant Cortex glia (CG) function led to light-inducible (LI) seizures in Ceramide phosphoethanolamine synthase ( cpes ) and temperature-sensitive (TS) seizures in zydeco ( zyd 1 ) mutants. Here, we have optimized Gal4/Split-Gal4/Gal80/LexA drivers to specifically express a gene of interest throughout development in CG subpopulations in different parts of the brain including optic lobe (OL), central brain (CB), and ventral nerve cord (VNC). Using these tools, we performed brain region–specific CG rescue experiments in cpes and zyd 1 mutants. We found that OL- and CB-specific, but not VNC-specific CG expression of CPES significantly suppressed LI seizures in cpes mutants. In contrast, VNC- but not OL- or CB-specific CG expression of ZYD suppressed TS seizures. In a third model, expression and activation of transient receptor potential, dTRPA1, exclusively in the VNC-specific CG was sufficient to induce TS seizures in wild-type flies. Our findings suggest that regionally specialized CG subtypes differentially regulate seizure susceptibility in seizure models.